Growth and Bioactive Compound Content of Glehnia littoralis Fr. Schmidt ex Miquel Grown under Different CO2 Concentrations and Light Intensities - Hye Ri Lee; Hyeon Min Kim; Hyeon Woo Jeong; Myung Min Oh; Seung Jae Hwang (Plants, 2020)
This study aims to determine the effect of different CO2 concentrations and light intensities on the growth, photosynthetic rate, and bioactive compound content of Glehnia littoralis Fr. Schmidt ex Miquel in a closed-type plant production system (CPPS). The plants were transplanted into a deep floating technique system with recycling nutrient solution (EC 1.0 dS·m-1 and pH 6.5) and cultured for 96 days under a temperature of 20 ± 1 °C, a photoperiod of 12/12 h (light/dark), and RGB LEDs (red:green:blue = 7:1:2) in a CPPS. The experimental treatments were set to 500 or 1500 µmol∙mol−1 CO2 concentrations in combination with one of the three light intensities: 100, 200, or 300 µmol∙m−2∙s−1 photosynthetic photon flux density (PPFD). The petiole length of G. littoralis was the longest in the 500 µmol∙mol−1 CO2 concentration with the 100 µmol∙m−2∙s−1 PPFD. The fresh weight (FW) and dry weight (DW) of shoots and roots were the heaviest in the 300 µmol∙m−2∙s−1 PPFD regardless of the CO2 concentration. Higher CO2 concentrations and light intensities produced the greatest photosynthetic rates. However, the SPAD value was not significantly different between the treatments. Higher light intensities produced greater content per biomass of chlorogenic acid and total saponin, although the concentration per DW or FW was not significantly different between treatments. The first and second harvest yields were the greatest in the 300 µmol∙m−2∙s−1 PPFD, regardless of the CO2 concentration. These results show that the 300 µmol∙m−2∙s−1 PPFD enhanced the growth, photosynthetic rate, and bioactive compound accumulation of G. littoralis, regardless of the CO2 concentration in a CPPS.